A Case of Giant Proliferative Periocular Pyogenic Granuloma. (4th May 2022) - Zehra, Fatima; Al-Tarrah, Khaled; GovindanSrinivasan, Karthikeyan; McMillan, Kevin; Nishikawa, Hiroshi; Hejmadi, Rahul; Jagadeesan, Jagajeevan
ABSTRACT: Pyogenic granuloma (PG) is a common vascular anomaly affecting the skin with occasional involvement of mucosa. Ophthalmic surgeons typically encounter these lesions as solitary, bright red, rapidly growing papules following surgery or trauma to the conjunctiva, e.g. chalazion, strabismus, or enucleation surgery. We present a rare and novel case of a disfiguring proliferative & eruptive giant pyogenic granuloma involving both mucosal and non-mucosal tissue of the ocular adnexa in the absence of any previous surgery, trauma, or medical history in a previously fit and well 43-year-old male. We demonstrate the histological features of the lesion following successful management with surgical excision & primary closure. The authors advocate surgery as the gold standard for managing such proliferative lesions ensuring low recurrence rates and histological confirmation for a lesion whose differential diagnoses include malignant eyelid lesions such as keratoacanthoma and squamous cell carcinoma.